Technique for Darkening of Extracted Teeth Simulating Pulpal Necrosis Discoloration - Paini TRD; Uchimura JYT; Sato F; Medina Neto A; Shimauti ELT; Baesso ML; Hidalgo MM; dos Santos MLA; Previdelli ITS; Pascotto RC (Dove Medical Press, 2022)
Thais RD Paini,1 Joana YT Uchimura,1 Francielle Sato,2 Antonio Medina Neto,2 Eliana LT Shimauti,3 Mauro L Baesso,2 Mirian M Hidalgo,1 Marcia LA dos Santos,4 Isolde TS Previdelli,4 Renata C Pascotto1 1Department of Dentistry, State University of Maringa, Maringá, PR, Brazil; 2Department of Physics, State University of Maringa, Maringá, PR, Brazil; 3Department of Clinical Analysis and Biomedical Science, State University of Maringa, Maringá, PR, Brazil; 4Department of Statistics, State University of Maringa, Maringá, PR, BrazilCorrespondence: Renata C Pascotto, Department of Dentistry, State University of Maringa, Av. Mandacaru 1.550, Maringá, PR, 87080-000, Brazil, Tel +55 44 99820215, Fax +55 44 30319051, Email renatapascotto@gmail.comBackground: The use of discolored teeth is required to test whitening products, and it is difficult to obtain them, given their scarcity.Objective: To present a technique for in vitro darkening of extracted teeth simulating pulpal necrosis discoloration.Materials and Methods: Hemolysates I and II from human blood were subjected or not to laser irradiation (442 nm) for 1 h. The concentration of oxyhemoglobin (O2Hb) was analyzed by ultraviolet/visible spectroscopy, and the conversion of O2Hb to methemoglobin (MetHb) by transmission spectroscopy was assessed immediately and after 3 and 40 days. For darkening evaluation, bovine incisors were divided into two groups (n = 25), and their pulp chambers were filled with hemolysate solution II (HSII) and hemolysate II solution + laser (HSII+L). After storage in artificial saliva for 40 days at 37°C, color changes were measured by a colorimeter and ΔE was compared with the NBS parameters. Data were analyzed using a mixed linear model (α=5%).Results: HSII+L presented the lowest O2Hb and higher MetHb. The conversion of O2Hb to MetHb in HSII+L was 42% higher than in HSII. Both groups were effective in darkening the teeth, according to the NBS. Darkening stabilized from day 35. HSII promoted a marked color difference.Conclusion: The proposed technique was effective in darkening the extracted teeth simulating necrosis discoloration for in vitro models.Graphical Abstract: Keywords: teeth, blood, colorimetry, hemoglobin, spectroscopy